Magnitude of Prelacteal Feeding and Its Associated Factors among Mothers Having Children Less than One Year of Age: A Community-Based Cross-Sectional Study in Rural Eastern Zone, Tigray, Ethiopia - Senait Gebreslasie Gebremeskel; Tesfay Tsegay Gebru; Selam Shushay Kassahun; Berhanu Gebresilassie Gebrehiwot (Hindawi Limited, 2020)
Background. Prelacteal feeding is an obstacle to optimal breastfeeding practices in developing countries. It directly or indirectly affects the health of the infants. Despite its importance, this issue has received little attention in Ethiopia. As a result, this study aimed to assess prelacteal feeding and associated factors among mothers of children aged less than 12 months in the rural eastern zone, Tigray, Ethiopia. Methods. Community-based cross-sectional study design was employed. The final sample size was 828, and the multistage sampling technique was used. Pretested and structured interviewer-administered tool was used for data collection. Data were entered, coded, and cleaned by Epi-Info version 7 and analyzed by using SPSS 22.0. Multivariable logistic regression was used to control the effect of confounding. Results. Eight hundred three mothers participated in this study. During the first three days after birth, 198 (24.7%) mothers practiced prelacteal feeding. Parity (AOR: 1.52, 95% CI: 1.04-2.23), late initiation of breastfeeding (AOR: 1.83, 95% CI: 1.30-2.59), and colostrum discard (AOR: 1.57, 95% CI: 1.06-2.33) were strongly associated with prelacteal feeding practice. Conclusion and Recommendation. One-fourth of participants practiced prelacteal feeding. Late initiation of breastfeeding, colostrum discard, and parity were significant determinants of prelacteal feeding. Awareness creation and health education concerning the advantages of early initiation of breastfeeding and the importance of colostrum during their health visits is necessary.